Actividades manuales y la escritura en niños de la Institución Educativa Inicial N° 311 Divino Niño, San Pablo 2022 - Flores Aspajo, Armilda (2023)
This research was developed with the objective of demonstrating the degree of relationship between manual activities and writing in children of the Initial Educational Institution No. 311 Divino Niño San Pablo 2022. The research is correlative, with a cross-sectional field design. The studied population consisted of boys and girls of both sexes. Observation was used as a technique and an observation guide as a tool to obtain the data, previously the tools were validated by expert judgment. The conclusion There is a high level of relationship between manual activities and writing in children of the initial. As verified with Spearman's Rho coefficient, which is (rs=0.592*; Sig. < 0.05), this coefficient indicates a moderate correlation and positive